2017
DOI: 10.1097/j.pain.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Opioid Safety Initiative on opioid-related prescribing in veterans

Abstract: The Veterans Health Administration (VHA) designed the Opioid Safety Initiative (OSI) to help decrease opioid prescribing practices associated with adverse outcomes. Key components included disseminating a dashboard tool that aggregates electronic medical record data to audit real-time opioid-related prescribing and identifying a clinical leader at each facility to implement the tool and promote safer prescribing. This study examines changes associated with OSI implementation in October 2013 among all adult VHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
125
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 21 publications
3
125
0
3
Order By: Relevance
“…26,27 In general, these efforts involve adoption of guidelines and monitoring of adherence with data collection. A retrospective 5-year analysis of the impact of standard statewide prescribing guidelines for ED clinicians in Ohio demonstrated a 39.7% decrease in total number of prescriptions and a 28.3% decrease in prescriptions of more than 3 days of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In general, these efforts involve adoption of guidelines and monitoring of adherence with data collection. A retrospective 5-year analysis of the impact of standard statewide prescribing guidelines for ED clinicians in Ohio demonstrated a 39.7% decrease in total number of prescriptions and a 28.3% decrease in prescriptions of more than 3 days of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…; Gellad, Good, and Shulkin ; Lin et al. ). Opioid and benzodiazepine co‐prescribing within the VA has also decreased consistently year over year (Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid and benzodiazepine co‐prescribing within the VA has also decreased consistently year over year (Lin et al. ). However, when accounting for non‐VA prescriptions, we observed proportions of veterans receiving concurrent prescription opioids and benzodiazepines that remained consistent across years, suggesting that some veterans may be making up the difference using non‐VA providers to supplement VA prescriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is especially relevant because opioid use and misuse have become an epidemic in the United States and the VA initiated the Opioid Safety Initiative in 2014 to attempt to combat it among Veterans (Lin et al. ). Using the linked VA and OHA PDMP data afforded Carlson and colleagues the ability to address this issue among a younger, lesser‐studied population and found that more than one‐third of Veterans who received opioids or sedative‐hypnotics from the VA had also received these prescriptions from non‐VA prescribers at some point during the study period.…”
mentioning
confidence: 99%